2023
DOI: 10.3389/fsurg.2023.1080143
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical site infection following reconstructive flap surgery: A multi-institutional analysis of 37,177 patients

Abstract: PurposeRates of surgical site infection (SSI) following reconstructive flap surgeries (RFS) vary according to flap recipient site, potentially leading to flap failure. This is the largest study to determine predictors of SSI following RFS across recipient sites.MethodsThe National Surgical Quality Improvement Program database was queried for patients undergoing any flap procedure from years 2005 to 2020. RFS involving grafts, skin flaps, or flaps with unknown recipient site were excluded. Patients were stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Longer operating time was also identified as a predictor of complications for microsurgical flap reconstruction. 20 34 35 36 37 In a previous study by Wong et al on 639 patients who underwent microsurgical free flap reconstruction, those with longer operating times were twice as likely to develop flap failure. 36 In our study population, only one patient experienced flap failure following phalloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Longer operating time was also identified as a predictor of complications for microsurgical flap reconstruction. 20 34 35 36 37 In a previous study by Wong et al on 639 patients who underwent microsurgical free flap reconstruction, those with longer operating times were twice as likely to develop flap failure. 36 In our study population, only one patient experienced flap failure following phalloplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing free flap reconstruction for the head and neck, race was an independent predictor of increased risk for SSI. 20 Using multivariate analysis, other studies highlight male gender and Black/African American race as predictors of increased risk for sepsis after reconstructive surgeries. 19 Our cohort reaffirmed the racial inequities reported in previous reconstruction literature.…”
Section: Discussionmentioning
confidence: 99%
“…In Hassan et al, predictors of SSI after flap reconstruction were identified and stratified by anatomic site. Among patients undergoing free flap reconstruction for the head and neck, race was an independent predictor of increased risk for SSI 20 . Using multivariate analysis, other studies highlight male gender and Black/African American race as predictors of increased risk for sepsis after reconstructive surgeries 19 .…”
Section: Discussionmentioning
confidence: 99%
“…LASSO analysis was used to screen the variables in this study owing to various clinical variables in the patient data. Compared to other models established solely using logistic regression 2 , this optimised model is less complex and helps physicians develop personalised treatment plans to minimise the risk of SSI in patients undergoing gastrointestinal surgery. This study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Infection can involve the skin at the site of the incision (superficial incision SSI), underlying tissues and muscles (deep incision SSI) or spread further into organs and/or spaces between organs (organ/space SSI). SSIs are among the most common nosocomial infections, accounting for ~20% of all hospital-acquired infections 2 . As a serious postoperative complication, SSI can lead to prolonged hospital stay, delayed wound healing, impaired tissue repair and flap necrosis, resulting in graft failure 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%